Integration of Artificial Intelligence in Geography Learning: Challenges and Opportunities - Rakuasa, Heinrich (Yayasan Sinergi Kawula Muda, 2023)
This research discusses the potential and challenges of integrating Artificial Intelligence (AI) in geography learning. By considering the fundamentals of AI and the role of geography in the era of globalization, this research outlines the benefits of AI in geography learning through interactive visualization and personalization of learning. However, challenges such as equitable access to technology and teacher training are major concerns in the application of AI. The research uses descriptive method with literature review which involves collecting, analyzing, and explaining the information in the literature relevant to the integration of artificial intelligence (AI) in Geography learning. In addition, this study highlights the opportunities of AI in geographic data analysis and addressing global challenges such as climate change. The profound implications of AI integration in geography learning are also discussed, given its impact on education and society. This research provides a holistic picture of the intersection of AI and geography, encouraging a better understanding of its potential and limitations. It is hoped that this research will provide guidance for educational practitioners and researchers to optimize the potential of AI in geography teaching, taking into account the challenges to be overcome and the opportunities to be exploited.